Changes in Umbilico-Placental Circulation during Prolonged Intact Cord Resuscitation in a Lamb Model - Kévin Le Duc; Estelle Aubry; Sébastien Mur; Capucine Besengez; Charles Garabedian; Julien De Jonckheere; Laurent Storme; Dyuti Sharma (MDPI AG, 2021)
Some previous studies reported a benefit to cardiopulmonary transition at birth when starting resuscitation maneuvers while the cord was still intact for a short period of time. However, the best timing for umbilical cord clamping in this condition is unknown. The aim of this study was to explore the duration of effective umbilico-placental circulation able to promote cardiorespiratory adaptation at birth during intact cord resuscitation. Umbilico-placental blood flow and vascular resistances were measured in an experimental neonatal lamb model. After a C-section delivery, the lambs were resuscitated ventilated for 1 h while the cord was intact. The maximum and mean umbilico-placental blood flow were respectively 230 ± 75 and 160 ± 12 mL·min−1 during the 1 h course of the experiment. However, umbilico-placental blood flow decreased and vascular resistance increased significantly 40 min after birth (p < 0.05). These results suggest that significant cardiorespiratory support can be provided by sustained placental circulation for at least 1 h during intact cord resuscitation.